2004
DOI: 10.1152/ajpcell.00558.2003
|View full text |Cite
|
Sign up to set email alerts
|

The tight junction: a multifunctional complex

Abstract: Multicellular organisms are separated from the external environment by a layer of epithelial cells whose integrity is maintained by intercellular junctional complexes composed of tight junctions, adherens junctions, and desmosomes, whereas gap junctions provide for intercellular communication. The aim of this review is to present an updated overview of recent developments in the area of tight junction biology. In a relatively short time, our knowledge of the tight junction has evolved from a relatively simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
1,018
3
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,244 publications
(1,047 citation statements)
references
References 167 publications
13
1,018
3
13
Order By: Relevance
“…Kidneys are composed of hundreds of thousands of functionally independent units called nephrons, and each nephron independently controls its own permeability and solute transport capabilities by changing its adhesive characteristics on the basis of external signals. The normal function of nephrons highly depends on epithelial cellecell adhesion and the surrounding extracellular matrix, 16,37 and adhesion molecules such as cadherins and integrins are key mediators of adhesion. 38,39 Our data indicate that TMIGD1 regulates kidney epithelial cell permeability because overexpression of TMIGD1 increased TEER and reduced permeability; reducing expression of TMIGD1 abrogated TEER.…”
Section: Discussionmentioning
confidence: 99%
“…Kidneys are composed of hundreds of thousands of functionally independent units called nephrons, and each nephron independently controls its own permeability and solute transport capabilities by changing its adhesive characteristics on the basis of external signals. The normal function of nephrons highly depends on epithelial cellecell adhesion and the surrounding extracellular matrix, 16,37 and adhesion molecules such as cadherins and integrins are key mediators of adhesion. 38,39 Our data indicate that TMIGD1 regulates kidney epithelial cell permeability because overexpression of TMIGD1 increased TEER and reduced permeability; reducing expression of TMIGD1 abrogated TEER.…”
Section: Discussionmentioning
confidence: 99%
“…4 Increased intestinal permeability appears to be an early biologic change that precedes the onset of autoimmune diseases, including CD and type I diabetes. 8,23,24 The peculiarity of CD is that it is the only autoimmune disease for which the triggering environmental factor gliadin is known.…”
Section: Discussionmentioning
confidence: 99%
“…3 Under physiologic conditions, access of gliadin to gutassociated lymphoid tissue is prevented by competent intercellular tight junctions (TJ) that limit passage of macromolecules (including gliadin peptides) across the intestinal epithelial barrier. 4 In susceptible individuals, however, the interplay between the initiating stimulus (eg, gliadin) and intestinal cells triggers TJ disassembly. It has been hypothesized that this is an early biologic change that precedes the onset of gliadin-induced immune events that eventually lead to the pathology associated with CD.…”
mentioning
confidence: 99%
“…Numerous agents and cell signaling pathways interact with the TJ protein complex [21,22] and the involvement of kinases in the biogenesis and regulation of the TJ components is well established [23][24][25][26][27][28]. Interestingly, several studies have demonstrated the involvement of various kinases in the phosphorylation and regulation of claudin proteins [29][30][31][32][33][34][35][36][37], and we have recently shown that phosphorylation of claudin-3 by PKA can affect TJ properties in ovarian cancer cells [38].…”
Section: Introductionmentioning
confidence: 95%